Factors contributing to successful patent ductus arteriosus closure with first pharmacological course - I Gusti Ayu Made Dwisri Okadharma; Ni Putu Veny Kartika Yantie; Eka Gunawijaya (Indonesian Pediatric Society, 2022)
Background Successful closure of patent ductus arteriosus (PDA) with ibuprofen or paracetamol as the first-line treatment has been reported, but little is known about factors affecting the closure rate. Objective To identify the closure success rate and contributing factors affecting a first course of pharmacological treatment in neonates with PDA. Methods A retrospective study was conducted in infants with isolated PDA treated with either ibuprofen or paracetamol and admitted to our neonatal care unit from January 2017 until June 2020. Included infants had PDA on echocardiography and received ibuprofen or paracetamol therapy as the closure treatment. Oral ibuprofen was given at 10 mg/kg on first day, then 5 mg/kg on the 2nd and 3rd days; while paracetamol was given intravenously 15 mg/kg every 6 hours for 3 days. Echocardiographic evaluation was performed 3 days after first course of treatment. Results In total, 20 of 33 (60.6%) infants achieved PDA closure with the first course of treatment. Earlier age at the start of the first course of treatment (PR 7.7; 95%CI 1.2 to 47.7; P=0.035) and normal birth weight (PR 13.3; 95%CI 2.4 to 72.4; P=0.001) were significant factors contributing to PDA closure. However, PDA size did not affect closure rate (PR 2.0; 95%CI 0.4 to 8.5; P=0.46). Conclusion Pharmacological treatment seems to have a good success rate for PDA closure, with significant positive associations with earlier age at start of treatment and normal birth weight.